The Code of Colorado Springs: Comprising Article XX of the Constitution of the State of Colorado, the Charter, Amendments Thereto, and General Ordinances of the City of Colorado Springs, Colorado 273, § 501 (Frank Exline ed., 1914) - (:unkn) unknown (My University, 1914)
Prohibited the concealed carry of any pistol, revolver, Bowie-knife, dirk, or other deadly weapon. Prohibited the display or flourish of any deadly weapon in a threatening or boisterous manner.
Keywords: BRANDISHING; CARRY - CONCEALED